Challenges of Hadith Studies in a Global World - Muadhir Muadhir; Ahmad Mohammad Tidjani (Taqriri: Journal of Al-Hadith Science Studies, 2025)
As the second source of Islamic teachings after the Qur'an, the Hadith holds a central position in shaping the laws, morals, and outlook on life of Muslims. Entering the global era, the study of Hadith faces both new challenges and opportunities. On the one hand, Orientalist criticism since the 19th century has opened up space for academic discussion, but often clashes with Islamic epistemology. Scholars' responses to this criticism have not only been defensive but also methodological innovation, the digitization of Hadith, and the strengthening of digital literacy. Another challenge arises from the currents of globalization, which have triggered the spread of fabricated Hadith, the reduction of context, and the commodification of religion, thus demanding increased literacy and communication ethics in the dissemination of Hadith. Furthermore, Hadith education plays a crucial role in strengthening interfaith dialogue in Indonesia's multicultural society by emphasizing universal human values. The prospects for Hadith studies in the global era are increasingly open through digitalization, strengthening academic programs, and interdisciplinary approaches that make Hadith more contextual and relevant to modern issues. With a strong tradition of Islamic scholarship and the experience of living in diversity, Indonesia has a significant opportunity to become a center of reference for the development of Hadith studies globally.